Immature Stages of Aspidolea singularis (Coleoptera: Scarabaeidae: Cyclocephalini) - NEITA-MORENO, JHON CÉSAR; RATCLIFFE, BRETT; CALBERTO, GERMAN (Revista Colombiana de Entomología, 2007)
The larva and pupa of Aspidolea singularis (Scarabaeidae: Dynastinae: Cyclocephalini) are described for first time based on specimens from Colombia. A key to the known third instar larvae of genera in the tribe Cyclocephalini is included. Data on the larval biology of Aspidolea singularis are provided.